Program terpadu penanggulangan kemiskinan di Kota Surabaya - Erna Setijatiningrum (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Surabaya is one of metropolitan city in Surabaya, yet still has a high poverty rates. This research aims to design an integrated program in reducing poverty in Surabaya. The high poverty rates lead to several complex problems such as unemployment, education, health, crime and social problem. Actually, a lot of poverty alleviation programs have been implemented by the municipal government of Surabaya. However, the program is still less effective because: 1) there is lack of coordination among agencies in running the program and 2) the program does not reflect the needs of the poor to a decent life in urban areas. This research employs qualitative method carried out in several governmental bodies relating to the issue of poverty alleviation. The result of this study indicates that there are eight priority needs of the poor, namely (1) education, (2) health, (3) housing, (4) nine basic needs, (5) clean water, (6) ease of administration, (7) training expertise, and (8) employment. From the eight priority needs of the poor, we found design of integrated program of poverty reduction which requires good coordination among relevant agencies. There are eight institutions which government agency should coordinate in the integrated program, namely (1) the Department of Education, (2) Social Service, (3) Departement of Health, (4) the Ministry of Community Empowerment, (5) Department of housing, planning, and urban development (6) Water Supply Company, (7) Department of Civil and Population, (8) the Ministry of Labour.